Implementasi Supervisi Akademik Kepala Sekolah Kinerja Guru dan Mutu Pendidikan di SDN.Plawad III Karawang - Utik Surtika Dewi (Journal on Education, 2023)
The formulation of the problem in this research is how the principal implements improving teacher performance at SDN Plawad III, East Karawang District, Data collection techniques use practice, observation, interviews and documentation. Data analysis techniques are: data collection, data reduction, data presentation and drawing conclusions, The results of the research show that the supervision program and instruments for carrying out supervision are owned by SDN Plawad III, East Karawang District. with the highest Teacher Competency Score (NKG) 81.67 and the lowest 75.00 while the highest Teacher Competency Assessment (PK GR) 83.93 and the lowest 70.62, (a) This means that the better the teacher's professionalism, the better the quality of education, (b) There is a joint positive and significant influence between the principal's academic supervision and teacher performance on the quality of education at the Plawad III public elementary school in Karawang Regency, amounting to 91.25%. This means that the better the principal's academic supervision and the better the teacher's performance, the better the quality of education.